GA.KIN.AG EMṢU im Hethitischen - Fritzsche, Elifta (Altorientalische Forschungen, 2011)
The Akkadogram EMṢU , meaning “sour” in Akkadian, frequently occurs in Hittite texts either directly before or (more often) after the Sumerogram GA.KIN.AG “cheese”. H. Zimmern proposed as part of a lexical article that in this context EMṢU should be translated as “Hefe”, adding F. Sommer’s tentative suggestion “oder Lab?”. Over the years, for reasons unknown, F. Sommer’s free association became the most accepted translation. The present paper evaluates the plausibility of F. Sommer’s proposal, discussing the related realia and examining the results when applied to Hittite texts of different genres. In taking up H. Zimmern’s suggestion, I propose a broader lexical range of “baking agent”, thus yielding a new translation for the noun EMṢU in Hittite texts, namely “sourdough”.